Pharmacoeconomic Analysis of Antiplatelet Therapy in the Treatment of Acute Coronary Syndrome and Diabetes Mellitus in Ukraine - Korzh, Iuliia V. (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: This study aims to improve the results of treatment patients with acute coronary syndrome (ACS) and diabetes mellitus (DM) using more effective antiplatelet therapy. Materials and Methods: It was analyzed the Cochrane database, the randomized, double-blind PLATO study, comparing the use of cyclooxygenase inhibitors in combination with ticagrelor (180 mg once, followed by 90 mg 2 g/day) and clopidogrel (300 or 600 mg once, with subsequent administration of 75 mg 1 g/day) in the treatment of patients with ACS and DM. Cyclooxygenase inhibitors prescribed 300 mg once, followed by appointment 75â€“100 mg 1 p/day. It was carried out the cost-effectiveness analysis based on the results of a randomized clinical trial and one-factor sensitivity analysis. Results and Discussion: The results of the â€œcost-effectivenessâ€ analysis of antiplatelet therapy in treating patients with ACS and DM in Ukraine showed the most favorable is the scheme with clopidogrel. To achieve a unit of efficiency in the case of application of scheme with ticagrelor, it is necessary to attract 1398.30 dollars USA, and for the scheme with clopidogrel - 1335.12 dollars USA $ 1340.13 USA (ICER = $ 66.59/1 extra life saved). The study indicates if the wholesale price is reduced by 12%, the scheme with the ticagrelor becomes dominant. Conclusion: Research results are used to develop effective models of reimbursement value provided by theme dicaland pharmaceutical care for patients with diabetes and ACS for implementing social model of compulsory medical insurance in Ukraine.